Elizabeth Barrett Browning - Avery, Simon (Studies in eighteenth- and nineteenth-century literature., 2003)
This new study of Elizabeth Barrett Browning challenges the dominant cultural myths of the poet as a solitary recluse, self-exiled from the world of politics, by arguing that she was one of the most astute and politically-informed critics of the social and political events of her time.